General discussion: Trends in emissions concentrations - Altuwayjiri, Abdulmalik H.; Bloss, William J.; Harrison, RoyM.; Mihaylova, Lyudmila; Oyarzún Aravena, Andrea María; Aravena, Andrea M. Oyarzun; Pfrang, Christian; Schauer, Jamie; Slater, Jessica; Srivastava, Deepchandra; Styring, Peter; Wallington, Timothy J.; et al. (My University, 2021)
Christian Pfrang opened discussion of the introductory lecture by Luisa Molina by communicating: Many thanks for your excellent introductory lecture (DOI: 10.1039/d0fd00123f). I am particularly interested in the challenges associated with residential cooking emissions. You commented on the emissions asso